Application of the KWL (Know, Want to Know, Learned) Learning Model to Improve Students' Reading Comprehension - Baehaqi, Kholil (AIM: Journal of Islamic Education Management, 2023)
This research endeavors to augment the reading comprehension proficiency among eighth-grade students at SMP Tunas Pertiwi, Cirebon, focusing on the material of descriptive text. The research design adopts the Classroom Action Research framework, as conceptualized by Kemmis & McTaggart, encompassing four iterative stages: planning, acting, observing, and reflecting. The study unfolds through two meticulously executed cycles, each comprising two meticulously planned sessions. The research cohort comprises 36 eighth-grade students at SMP Tunas Pertiwi, Cirebon. The findings underscore the pivotal role played by the KWL model in fostering an enhancement in the reading comprehension capabilities of students, substantiated by a nuanced assessment involving average scores and completion percentages. Observational analyses conducted throughout the instructional phases employing the KWL model unveil the students' aptitude in discerning the social functions, textual structures, and linguistic intricacies inherent in a diverse array of oral and written descriptive texts. Their ability to provide and solicit information pertinent to straightforward text attests to the contextual mastery facilitated by this pedagogical approach. Analyzing the results of the reading comprehension test, the initial cycle reveals an average score of 73.77 with a completion percentage of 71.34%. Subsequently, in the second cycle, a notable improvement is observed with an average score of 82.44 and a completion percentage soaring to 89.27%. Consequently, the judicious implementation of the KWL model emerges as an efficacious means to elevate the reading comprehension skills of students, particularly in the realm of descriptive text material. Â Â